Asymtotics of the Module of Minimizers to a Ginzburg-Landau Type Functional (Journal of Partial Differential Equations, 2001)
The author proves that the module of minimizers for a Ginzburg-Landau type functional converges to 1. And the estimates on the convergent rate are also presented.